COGNITIVE IMPAIRMENT AND MEDICATION NONADHERENCE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Angianto, Alexander Randy; Yunir, Em; Herqutanto; Abdullah, Murdani; Sauriasari, Rani (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Poor glycemic control in patients with type 2 Diabetes Mellitus results in a variety of complications including cognitive impairment. To implement self-management, intact cognitive function is necessary. In a variety of chronic diseases, cognitive impairment has been associated with medication nonadherence. Nonetheless, no studies have looked into the relationship between the two in patients with type 2 DM in Indonesia. This study aimed to determine the relationship of cognitive impairment with medication nonadherence in patients with type 2 DM. METHODOLOGY The design of this study was cross-sectional with 96 study subjects with type 2 DM older than 18 years old in the outpatient unit at Tebet District General Hospital. Demographic characteristics, clinical parameters, cognitive function assessment, and medication adherence use were fully documented. Cognitive function was assessed with the Indonesian version of the Montreal Cognitive Assessment (MoCA-Ina). Medication adherence was assessed using pill count. RESULTS There were 69.9% of the research subjects with cognitive impairment with education level as an associated factor (OR 5.223; 95% CI 1.99-12.22). Analysis of the occurrence of impairment of the function of memory domain 96.9%; executive 78%, visuospatial 78%; attention 30%; language 26%; and 4.2% orientation. Medication non-adherence was found in 26% of the study subjects. Bivariate analysis did not show an association between cognitive impairment and medication non-adherence. (OR 0.757 95% CI [0.280-2,051] p=0,58). CONCLUSION Cognitive impairment was found in 69,9% of patients with type 2 DM, and medication non-adherence was found in 26% of patients. Cognitive impairment was not associated with medication non-adherence in patients with type 2 DM.